Clinical and hemodynamic characteristics of cardiogenic shock complicating acute myocardial infarction - Thang, Pham Xuan; Minh, Nguyen Duy; Hoi, Dang Van; Dat, Nguyen Tien; Thu, Nguyen; Hung, Ha Tran; Chi, Nguyen Van; Quan, Nguyen Huu; Tuan, Nguyen Anh (Tạp chí Nghiên cứu Y học, 2026)
Among 84 patients with cardiogenic shock classified as Society for Cardiovascular Angiography and Interventions (SCAI) stage D–E, the in-hospital mortality rate was 29.8%. Mixed venous oxygen saturation (SvO2) was associated with in-hospital mortality, with an optimal cutoff value of ≤55%. Patients with a cardiac power output (CPO) <0.535 W exhibited higher in-hospital mortality. These findings suggest that SvO2 and CPO may provide additional value for early risk stratification among patients with cardiogenic shock complicating acute myocardial infarction, even within the same SCAI stage.